The selenium and vitamin E status of horses in Prince Edward Island - Muirhead, Tammy L. (Canadian Veterinary Medical Association, 2010)
Serum selenium (Se), vitamin E, and resting thyroid hormone concentrations were measured in 201 horses in Prince Edward Island (PEI). Selenium concentrations were either marginal (0.0053 to 0.1200 ppm) or deficient (< 0.0053 ppm) in 79% of horses based on current reference ranges for Se in serum. Aged and young adult pleasure horses had a higher prevalence of inadequate Se concentrations compared to racehorses and broodmares (82% and 97% versus 45% and 72%, respectively). Overall, 13% of horses had inadequate (< 200 μg/dL) serum vitamin E concentrations; most of these were young pleasure horses. No horses were hypothyroid and, contrary to findings in other species, there was a positive relationship between serum thyroxine and Se concentrations (P < 0.05). We conclude that Se deficiency is widespread in PEI horse populations, especially in pleasure horses, and vitamin E deficiency is more common in young pleasure horses. Micronutrient supplementation practices employed by PEI horse owners appear inadequate to ensure sufficiency.